A case study - Regulation and Functional Mechanisms of Cancer Cells and Control its Activity Using Plants and their Derivatives - Gaanty Pragas, Maniam; Kuppusamy, Palaniselvam; M. M., Yusoff; Natanamurugaraj, Govindan (Elsevier, 2013)
Novel exploiting to the understanding of conventional medicine was followed by the findings of many unique secondary metabolites and its biological property and is highly required for treating of many endemic diseases. The plants have been a long background in ethno pharmacological knowledge for treatment of endemic and non-endemic diseases. Such plants are traditionally used in different form of paste, extraction and powder to treat seasonal diseases. Nowadays main uses of some medicinal plants have been a great deal with cure and control various chronic diseases such as cancer, AIDS, hepatitis, neurogenic disorders and acute kidney diseases. Cancer is molecular dysfunction and disarrangement in DNA base pairs it leads to change the human physiological and biochemical behavior of the system. Apoptotic mechanisms are regulating by two distinct pathways in which basic creeds perform in common to all eukaryotes. The key components in apoptosis especially mitochondrial intracellular organelles are identified (DNA, protein and ATP, Ca2+). These components control the next cellular binder step and participate in effecting cell suicide mechanisms. The diverse aspects of mitochondria involved in apoptosis include dealing with other proceedings such as release of protein or enzymes to effective for cell death. In these mechanism plants and related natural products using alternative therapeutic management, very less toxicity and cost benefits. Plant extracts and its biomass has revealed the existing of various pharmacologically active compounds like steroids, polyphenols, polysaccharides, saponins, alkaloids, tannins and terpenoids. The reliable natural products are acting as high sources for anticancer drugs. The natural derived compounds are the prolongation of life span of the zeolites and decrease of malignancy cell formation in the cellular system.